Aussenpolitische dokumente der Republik Österreich 1918-1938 (ADÖ) (Wien : München Wien : München Wien : München Wien : München Wien : München Wien : München Wien : München Wien Wien Wien)
12 cilt (1. c. 534 sayfa ; 2. c. 504 sayfa ; 3. c. 675 sayfa ; 4. c. 518 sayfa ; 5. c. 568 sayfa ; 6. c. 516 sayfa ; 7. c. 424 sayfa ; 8. c. 348 sayfa ; 9. c. 490 sayfa ; 10. c. 459 sayfa ; 11. c. 272 sayfa ; 12. c. 398 sayfa)